2002
DOI: 10.1152/ajpheart.00275.2002
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of cardiac protein kinase B is regulated by palmitate

Abstract: In this study isolated perfused working rat hearts were used to investigate the role of palmitate-regulated protein kinase B (PKB) phosphorylation on glucose metabolism. Rat hearts were perfused aerobically in working mode with 11 mM glucose and either 100 microU/ml insulin or 100 microU/ml insulin and 1.2 mM palmitate. PKB activity and phosphorylation state were reduced in the presence of 1.2 mM palmitate, which correlates with a decrease in glycolysis (47%), glucose oxidation (84%), and glucose uptake (43%).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
51
0
1

Year Published

2003
2003
2008
2008

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 43 publications
3
51
0
1
Order By: Relevance
“…We examined through which of the postreceptor signaling pathways insulin provoked an increase in total FAT/ CD36 content. As has been shown previously (26,29), exposure (5 min) of cardiac myocytes to insulin increased the phosphorylation of Akt (Ser 473 and Thr 308 ), ERK1/2, and PKC / , and these insulin-induced phosphorylations were blocked by LY-29004, UO-126, and PKC-ps, respectively (data not shown). Blocking of the PKC / -signaling pathway did not inhibit the insulin-induced expression of FAT/CD36 (P Ͼ 0.05; Fig.…”
Section: Effects Of Insulin On Subcellular Distribution Of Fat/cd36 Asupporting
confidence: 82%
See 1 more Smart Citation
“…We examined through which of the postreceptor signaling pathways insulin provoked an increase in total FAT/ CD36 content. As has been shown previously (26,29), exposure (5 min) of cardiac myocytes to insulin increased the phosphorylation of Akt (Ser 473 and Thr 308 ), ERK1/2, and PKC / , and these insulin-induced phosphorylations were blocked by LY-29004, UO-126, and PKC-ps, respectively (data not shown). Blocking of the PKC / -signaling pathway did not inhibit the insulin-induced expression of FAT/CD36 (P Ͼ 0.05; Fig.…”
Section: Effects Of Insulin On Subcellular Distribution Of Fat/cd36 Asupporting
confidence: 82%
“…Recent studies have provided evidence that different signaling pathways can contribute to protein synthesis in cardiac myocytes (15,32), and insulin can activate a number of signaling pathways (26,29). Blocking insulin signaling through the MAP kinase-and PKC / -signaling pathways failed to inhibit the insulin-induced increase in FAT/CD36 Fig.…”
Section: Fig 4 Effects Of Insulin On Fat/cd36 (A)mentioning
confidence: 98%
“…However, insulin did not appear to be present in the perfusate in the study of Irie et al, 21 which may have inhibited glucose uptake. 27 In addition, because the concentration of insulin used in our study was supraphysiological, it is possible that this high concentration of insulin may have beneficial effects on function by itself. 28 The presence of insulin in the perfusate may have increased cardiac glucose utilization, which could play a role in the improved performance observed in the FAT/CD36-KO hearts in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…The unsaturated FFA oleate increased PI3K activity, whereas the saturated FFA palmitate decreased it. Others have reported that the activity of Akt/PKB, the downstream target of PI3K, was reduced by palmitate treatment (54,55). Because downstream targets of the PI3K/Akt signaling pathway that have been identified include the inhibition of proapoptotic proteins Bad and Bax (56, 57), we initially hypothesized that palmitateinduced apoptosis might involve an activation of the proapoptotic Bcl-2 family proteins, resulting from the inactivation of the PI3K/Akt pathway.…”
Section: Discussionmentioning
confidence: 99%